Detection of Calmodulin-Binding Proteins Using a 32P-Labeled GST-Calmodulin Fusion Protein and a Novel Renaturation Protocol - Roland Fischer; Yu Wei; Martin Berchtold (BioTechniques)
To identify calmodulin-binding proteins in cellular extracts and tissue homogenates and to analyze purified calmodulin target proteins, overlay procedures using 125I-calmodulin or, more recently, nonradioactive biotinylated calmodulin have been widely used. Here we describe a rapid, alternative method for detecting calmodulin-binding proteins with a 32P-labeled calmodulin probe generated as a glutathione-S-transferase (GST)-fusion protein. We used a modified pGEX-2TK vector, which contains the flag epitope and the consensus sequence RR- A-S, that can be phosphorylated by the cAMP-dependent protein kinase A. The fusion protein is easily purified from bacterial lysates by affinity chromatography using glutathione-Sepharose® 4B beads. Phosphorylation of GST-calmodulin is performed directly on the beads and, after elution with reduced glutathione, the labeled calmodulin probe can be used for overlay experiments. We also describe a rapid renaturation protocol that enhances the signal for some but not all calmodulin-binding proteins and is used after the proteins have been transferred to nitrocellulose filters. Furthermore, we have compared the specificity and sensitivity of the 32P-labeled GST-calmodulin overlay with those of 125I-calmodulin and biotinylated calmodulin, clearly indicating that our newly developed protocol is a suitable alternative to conventionally used calmodulin overlay procedures.